Pregnancy Outcomes in Thyroid Cancer Survivors: A Propensity Score-Matched Cohort Study - Cao, Qi; Zhu, Huili; Zhang, Jiani; Li, Yujing; Huang, Wei (Frontiers in Endocrinology, 2022)
Background: Many female thyroid cancer survivors develop the need of pregnancy after treatment. Current studies showed inconsistent results on pregnancy outcomes in these survivors. And detailed information on the pathological type, treatment and gestational thyroid function of the thyroid cancer survivors were not well declared, making the refined assessment of the impact of a history of thyroid cancer and related treatments on pregnancy outcomes challenging. Objective: To investigate the risk of adverse pregnancy outcomes in thyroid cancer survivors. Methods: This was a retrospective cohort study involving 96 women with a history of thyroid cancer and 192 women without any history of thyroid disease between January 2019 and June 2020 in West China Second University Hospital of Sichuan University. Propensity score matching (PSM) and logistic regression were used to control confounding variables. Results: Among the 21,410 women, pregnancy occurred in 96 women (0.45%) with a history of differentiated thyroid cancer. Compared to controls, survivors of thyroid cancer had higher levels of free thyroxine [15.47 (13.61-17.67) vs 14.38 (13.20-15.81) pmol/ml; P<0.001], higher levels of thyroid peroxidase antibodies (TPOAb) (43.55 (31.43-71.43) vs 35.95 (28.00-48.03) U/ml; P, 0.008), similar levels of thyroid stimulating hormone [1.46 (0.56-3.15) vs 1.36 (0.81-1.92) mIU/ml; P, 0.142]. There were no significant differences in adverse pregnancy outcomes between survivors and controls. Foetal macrosomia was lower among survivors (OR, 0.077; 95% CI, 0.009-0.668; P, 0.020). Additionally, survivors had reduced weight gain during pregnancy [13.0 (10.0-15.0) vs 14.00 (11.00-16.00) kg; P, 0.005] and reduced placental weight [563.0 (514.5-620.0) vs 572.0 (520.0-650.0) g; P, 0.019], albeit with small absolute differences. Radioactive iodine therapy (n=33) did not adversely affect pregnancy outcomes. Conclusion: A history of treated differentiated thyroid cancer was not associated with adverse pregnancy outcomes.